(untitled) (Revista de Estudos da Linguagem, 2020)
Abstract: This paper aims to discuss both a typology of articulation between verbal and pictorial modalities in the construal of metaphors and the potential pragmatic and rhetorical effects of the activation of multimodal metaphors in practical argumentation. To do so, we analyze six texts from governmental health campaigns in Brazil oriented towards the elimination of Aedes aegypti breeding grounds, the mosquito mainly responsible for the transmission of dengue fever, chikungunya and zika in the country. In terms of the expression of metaphorical vehicles and topics in each modality, we could identify, as a result, three main modes of articulation: autonomy, correlation and interdependence. For each mode, we showed some pragmatic and semantic effects, such as increasing metaphoricity, inducing reframing and refining referentiality. We frame this discussion by critically considering a series of different frameworks on metaphor studies, such as Lakoff and Johnson (1980), Forceville (2007), Müller (2008), Vereza (2007, 2017, 2018), Gonçalves-Segundo and Zelic (2016) and Steen (2017). In terms of argumentative roles, we concluded that multimodal metaphors were relevant in construing the Negative Consequences of inaction in regard to the elimination of breeding grounds, hyperbolizing the lethal potential of the infections; in inducing the reader’s readiness and tendency towards working collectively to achieve the campaign’s intended Goals; and, finally, in generating humor in the construal of the campaign’s Motivating Circumstances, in order to draw the reader’s attention and identification towards this necessary social action. To support this debate, we drew mainly on Fairclough and Fairclough (2012), Macagno and Walton (2019) and Gonçalves-Segundo (2019). Keywords: multimodal metaphor; multimodality; metaphor; argumentation; practical argumentation. Resumo: Nosso objetivo, neste artigo, é discutir tanto uma tipologia de articulação entre as modalidades verbal e imagética na construção de metáforas quanto os potenciais efeitos pragmáticos e retóricos da ativação de metáforas multimodais na argumentação prática. Para isso, analisamos seis textos de campanhas governamentais de saúde brasileiras orientadas à eliminação de focos de reprodução do mosquito Aedes aegypti, o principal responsável pela transmissão da dengue, da chikungunya e da zika no país. No que diz respeito à expressão de veículos e tópicos metafóricos em cada modalidade, identificamos, como resultado, três principais formas de articulação: autonomia, correlação e interdependência. Para cada uma dessas formas, mostramos alguns efeitos semântico-pragmáticos, como aumento de metaforicidade, indução de reenquadramento e refinamento de referencialidade. Tecemos essa discussão a partir de um diálogo crítico com diversas perspectivas, em especial Lakoff e Johnson (1980), Forceville (2007), Müller (2008), Vereza (2007, 2017, 2018), Gonçalves-Segundo e Zelic (2016) e Steen (2017). Em termos de funções argumentativas, concluímos que as metáforas multimodais foram relevantes na construção das Consequências Negativas da inação no tocante à eliminação dos focos de reprodução do mosquito, hiperbolizando o potencial letal das infeções; na indução de um estado de prontidão e de trabalho coletivo no sentido de atingir os Objetivos da campanha; e, finalmente, em gerar humor na construção das Circunstâncias Motivadoras da campanha, para obter a atenção e a identificação do leitor em relação a essa ação social necessária. Para enquadrar esse debate, valemo-nos especialmente de Fairclough e Fairclough (2012), Macagno e Walton (2019) e Gonçalves-Segundo (2019). Palavras-chave: metáfora multimodal; multimodalidade; metáfora; argumentação; argumentação prática.